Consolidation of Digital Skill of Teaching in No-Online Learning in Pakistan - Masooma Kazam; Dr. Asma Islam; Ammara Asghar; Uzma Ashraf; Uzma Baigum; Dr. Shahzad Channa (Al-Qanṭara, 2022)
Abstract This research aims to determine secondary school teachers' perspectives about "digital skills accumulation in online learning." A descriptive quantitative study. The study aims to (1) analyse secondary school teachers' knowledge, attitude, and abilities of digital technologies, (2) find teachers' practises for increasing their digital skills, and (3) explore impediments to strengthening teachers' digital skills. The population was all Toba Tek Singh government secondary school teachers. Random sampling was used to acquire data from 300 teachers. The researcher created a Likert-scale questionnaire with 30 positive statements. Experts' comments and a pilot research ensured validity and dependability. The researcher obtained data from secondary school instructors after ensuring validity and dependability. Later, the same data was loaded into SPSS to calculate mean, standard deviation, frequency, and percentage. This survey found that most secondary school instructors favoured the learning of digital skills but had only moderate computer, internet, and digital skills knowledge. Online platforms, tools, YouTube, workshops, seminars, colleagues, students, and online communities help instructors improve their digital skills. Most teachers acknowledged digital inadequacies. Time, digital gadgets, internet connectivity, digital skills, and interest were issues. Educators commonly use digital gadgets in teaching and learning. Teachers' practises and digital skills are correlated (r=.757).